Olympians as laborers: how unionizing can help athletes bargain for compensation and better structural support - Farrag, S. (Fordham Intellectual Property, Media and Entertainment Law Journal, 2022)
Team USA athletes suffer poor structural support and inadequate compensation despite constituting irreplaceable labor for the multi-billion-dollar Olympic sports industry. This poor support is evident in recent complaints made by Olympic stars of the poor mental health support provided by the United States Olympic & Paralympic Committee and in its failure to prevent nearly two decades of sexual abuse perpetrated on USA Gymnastics gymnasts. The inadequate compensation is apparent as athletes continue to receive no wages for their participation in the Olympics or Olympic-sanctioned events, generally struggle financially, and face restrictions on licensing their name, image, and likeness to partners during the Olympics. Theoretically, athletes can challenge some of these problems through antitrust or employment law claims. However, relevant case law makes those paths difficult, at best. Several circuits have found an antitrust exemption for the United States Olympic & Paralympic Committee and similarly situated National Collegiate Athletic Associate athletes have failed thus far to hold the Association liable for wages under the Fair Labor Standards Act. The best path athletes can take to improve their lot comprehensively and holistically is labor law. Unionization can empower athletes to directly negotiate with the United States Olympic & Paralympic Committee in search of better structural support and adequate wages. The unionization process, however, will most likely result in athletes of many, but not all, sports gaining the ability to unionize. Others will fail to qualify as employees under the National Labor Relations Act or will be exempt as "independent contractors." Nonetheless, labor law is the most appropriate and efficient way to improve the lot of Team USA athletes as they pursue their dreams.